1976
DOI: 10.1136/jcp.29.5.441
|View full text |Cite
|
Sign up to set email alerts
|

Instability and linkage of silver resistance, lactose fermentation, and colony structure in Enterobacter cloacae from burn wounds.

Abstract: SYNOPSIS A strain of Enterobacter cloacae from a burn wound has displayed unstable resistance to silver nitrate and a linkage of this characteristic to that for rapid lactose fermentation and mucoid colony structure. Attempts to demonstrate transferability of these unstable determinants gave negative results.The use of silver preparations for topical antimicrobial therapy in the Burns Unit of this Hospital has prompted routine screening of bacterial isolates for resistance to this metal.During some early tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 6 publications
0
26
0
2
Order By: Relevance
“…These resistances are selected frequently when metal salts are used as antiseptics. Ag + -resistant bacteria have been reported periodically from sources such as hospitals and burn wounds where silver toxicity might be expected to select for resistance (Annear et al, 1976 ;Bridges et al, 1979 ;Hendry & Stewart, 1979 ;McHugh et al, 1975 ;Pruitt et al, 1998). The physiological, biochemical and molecular basis of bacterial Ag + resistance were not described prior to our studies .…”
Section: Some Metal Cations (Zn#mentioning
confidence: 99%
“…These resistances are selected frequently when metal salts are used as antiseptics. Ag + -resistant bacteria have been reported periodically from sources such as hospitals and burn wounds where silver toxicity might be expected to select for resistance (Annear et al, 1976 ;Bridges et al, 1979 ;Hendry & Stewart, 1979 ;McHugh et al, 1975 ;Pruitt et al, 1998). The physiological, biochemical and molecular basis of bacterial Ag + resistance were not described prior to our studies .…”
Section: Some Metal Cations (Zn#mentioning
confidence: 99%
“…Since the late 1960s, when silver compounds were routinely applied to burn wounds (e.g., silver sulfadiazine in Flamazine), mortality rates rapidly reduced to about 1/4 (35). A decade later, a series of studies reported silver resistance in Enterobacteriaceae and nonfermenters (3,6,20,33). Since that time, an increasing number of outbreaks due to silver-resistant strains of Enterobacteriaceae have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…(1,4). Staplz.ylococeus aureus türlerinin yapısındaki penisilinaz plazmidlcri antiman, arsenik, bizmut, kadmiyum, kurşun, civa ve çinko bileşiklerine karşı da mikroorganizmanın direnç göstermesini sağlamaktadır.…”
Section: Introductionunclassified